'Winter camp' 1917: integrated conflict archaeology on the Messines Ridge 1914-1918 (Belgium). Issue 2 (4th May 2022) - Gheyle, Wouter; Bourgeois, Jean; Note, Nicolas; Saey, Timothy; Van Eetvelde, Veerle; Van Meirvenne, Marc; Stichelbaut, Birger
ABSTRACT: Integrated research using aerial photography, proximal soil sensing, historical research and excavations of an unusual First World War site in Flanders (Belgium) is presented. Aerial photography revealed a grid of 5x6 huts unusually close to the front line. Geophysical research indicates good preservation of these structures. A targeted excavation was carried out. The results give insight into the structure of a military camp built in autumn 1917, used until the German offensive of April 1918. Research on excavated objects and historical sources revealed the camp was as the winter quarters for British and Australian pioneers. The unusual location and the fact that the pioneers occupied the camp themselves means that the huts found were not standard and dug in to provide extra protection. This research shows that barracks camps can be well preserved in the soil archives and have the potential to uncover stories from everyday life behind the front.